Imunohistochemická detekce exprese genu p53 a p21 v bunkách maligního melanomu uvey - Tokosová, E; Hermanová, M; Uhmannová, R; Smardová, J; Hlinomazová, Z (Ceska a slovenska oftalmologie, 2008)
AIM: To examine by means of immunohistochemistry the expression of the tumor suppressing gene p53 and gene p21 in cells of malignant melanoma of the uvea from formalin-paraffin material from patients, who were during the period 2000 - 2006 surgically treated due to malignant melanoma of the uvea at the Department of Ophthalmology in the University Hospital in Brno (Brunn), Czech Republic, E.U., and to correlate the results of the immunohistochemical detection with clinical signs of the tumor of each patient. METHODS: Twenty-nine malignant melanomas of the uvea were examined by means of monoclonal antibody DO-1 (Novocastra company) and all 29 samples of malignant melanoma of the uvea were immunohistochemically examined for the p21 gene expression by means of the monoclonal antibody SX 118 (DAKO company). We evaluated the percentage of positive nuclei and the intensity of the staining in immunohistochemically detected p53 and p21 genes expression. RESULTS: Results suitable for evaluation we obtained in 28 samples of malignant melanomas, one sample was not suitable for evaluation due to extremely high presence of melanin pigment. In 3 patients, weak nuclear p53 gene expression was detected in 5-15% of cells, in 1 patient, the very weak intensity of staining in 5-15% of cells was found. In three patients, in 5-15% of cells, weak expression of p21 gene, and in one patient, very weak expression of p21 gene in 5-15% of cells (in all 4 cases, the p53 expression was established) were found. In one of those 4 patients with p53 gene expression it was the malignant melanoma of the iris, in one of them it was malignant melanoma of the ciliary body, and in 2 of them it was malignant melanoma of the choroid. CONCLUSION: The expression of the p53 gene and the expression of the gene p21 were established in 4 out of 28 patients (14.3%). From the above-mentioned results we can assume that stabilizing mutations of p53 gene are rare in the melanoma of the uvea. The proved expression p53 in 4 patients is probably result of the expression of the standard (wild-type) p53 gene, especially according to the ability to induce the expression of p21 gene. In our group, there were not proved marked nuclear accumulation of p53, which would suggest the presence of p53 gene mutation.
Keywords: Gene Expression Regulation, Neoplastic; Tumor Suppressor Protein p53; Cyclin-Dependent Kinase Inhibitor p21; nádorový supresorový protein p53; Immunohistochemistry; regulace genové exprese u nádorů; Uveal Neoplasms; lidé; Genes, p53; melanom; geny p53; imunohistochemie; inhibitor p21 cyklin-dependentní kinasy; nádory uvey; Humans; Melanoma